Formation of Ecological Consciousness in Education - Maksudova Gulnora Mukhammadjonovna (Zien Journals, 2023)
Inculcating environmental awareness in children from a young age can be the first solution to prevent the unfortunate situations that occur in nature today.
Keywords: Education; environmental consciousness; ecological culture; social attitude